2012
DOI: 10.1038/ijo.2012.22
|View full text |Cite
|
Sign up to set email alerts
|

The frequent UCP2 −866G>A polymorphism protects against insulin resistance and is associated with obesity: a study of obesity and related metabolic traits among 17 636 Danes

Abstract: The UCP2 -866G-allele is associated with decreased insulin sensitivity in Danish subjects and is associated with obesity in a combined meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 61 publications
1
32
1
1
Order By: Relevance
“…The three commonly studied polymorphisms in the UCP2 gene are K866G/A polymorphism in the promoter region, the Ala55Val polymorphism in the exon 4 and the 45 bp insertion/deletion polymorphism in the 3 0 -UTR. These polymorphisms have been shown to be associated with various metabolic traits such as obesity (24), body fat distribution (25), resting energy expenditure (26), type 2 diabetes (10) and insulin resistance (9,27) in various populations from different ethnic backgrounds (24). However, there were also studies that failed to show an association between these polymorphisms and metabolic traits (8,28,29).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The three commonly studied polymorphisms in the UCP2 gene are K866G/A polymorphism in the promoter region, the Ala55Val polymorphism in the exon 4 and the 45 bp insertion/deletion polymorphism in the 3 0 -UTR. These polymorphisms have been shown to be associated with various metabolic traits such as obesity (24), body fat distribution (25), resting energy expenditure (26), type 2 diabetes (10) and insulin resistance (9,27) in various populations from different ethnic backgrounds (24). However, there were also studies that failed to show an association between these polymorphisms and metabolic traits (8,28,29).…”
Section: Discussionmentioning
confidence: 95%
“…Polymorphisms within the UCP2 gene have been shown to be associated with various metabolic traits such as obesity (8,9) and type 2 diabetes (10,11). Although the effects of these polymorphisms on UCP2 function are still unclear, it could be hypothesised that the loss-of-function polymorphisms are likely to contribute to type 2 diabetes as a result of lower hepatic glucose uptake (12).…”
Section: Introductionmentioning
confidence: 99%
“…Andersen et al . [13] performed a meta-analysis of 8 studies that analyzed the association between the UCP2- 886G/A polymorphism and obesity. In agreement with our data, they reported an association between the UCP2- 866A allele and protection for obesity in Europeans.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this data, Andersen et al . [13] published a meta-analysis showing an association between the UCP2- 866G/A polymorphism and obesity in subjects of European descent. Until this date, no meta-analysis evaluated the association of UCP polymorphisms with body mass index (BMI) variability.…”
Section: Introductionmentioning
confidence: 99%
“…This study has shown that the -866G-allele was associated with elevated fasting serum insulin levels and insulin resistance (HOMA index) and decreased insulin sensitivity in Danish subjects (Andersen et al, 2012). Furthermore, in a study performed with a Spanish group of 193 obese children and adolescents and 170 controls, Ochoa et al reported that the -55C>T (rs1800849) polymorphism of the UCP3 gene directly associated with higher fasting insulin levels and insulin resistance in heterozygous subjects from the control group.…”
Section: Impact Of Genetic Polymorphisms On Insulin Resistance 53mentioning
confidence: 98%